LoRa LPWAN propagation channel modelling in IIUM Campus - Masadan, Nurul Afifah; Habaebi, Mohamed Hadi; Yusoff, Siti Hajar (IEEE, 2018)
LoRa, one of the most outstanding low power wide area network (LPWAN) technology has unique and remarkable features. Because of its long-range coverage, low power consumption and low cost system architecture, LoraWAN has becoming a favorable option for performing communication in most of IoT wireless applications. This project aimed at quantifying the foliage effect in terms of attenuation and its overall contribution to the path-loss and link budget calculations. Specifically, five tree types were studied and their contribution to the path loss were quantified for different path crossings (e.g., trunk, tree-top and branches). The trees are Licuala Grandis, Mimusops Elengi, Mangifera Indica, Cyrtostachys Renda and Livistona Chinensis. Mimusops Elengi tree, characterized by its big size and crown density, gave the strongest mean foliage attenuation accumulating up to 20 dB. Trunks contribute even higher attenuation in comparison to tree-tops and branches. The Okumura/Hata, Log-normal shadowing and foliage models are used as references for this propagation models development. Our study showed that Okumura fails to capture the effect of foliage in International Islamic University Malaysia, Gombak campus that is rich in trees. This goes to illustrate the necessity for considering the tropical environment where the characterization of foliage attenuation plays an important role in determining the propagation model path-loss and link budget needed for LoRa network design and planning.